pH sensing via bicarbonate-regulated “soluble” adenylyl cyclase (sAC) - Rahman, Nawreen; Buck, Jochen; Levin, Lonny R. (Frontiers in Physiology, 2013)
Soluble adenylyl cyclase (sAC) is a source of the second messenger cyclic adenosine 3',5' monophosphate (cAMP). sAC is directly regulated by bicarbonate (HCO3-) ions. In living cells, HCO3- ions are in nearly instantaneous equilibrium with carbon dioxide (CO2) and pH due to the ubiquitous presence of carbonic anhydrases. Numerous biological processes are regulated by CO2, HCO3-, and/or pH, and in a number of these, sAC has been shown to function as a physiological CO2/HCO3/pH sensor. In this review, we detail the known pH sensing functions of sAC, and we discuss two highly-studied, pH-dependent pathways in which sAC might play a role.